PENGARUH TGT TERHADAP MOTIVASI BELAJAR SISWA KELAS IV MAPEL IPAS SD MUHAMMADIYAH AMBARBINANGUN YOGYAKARTA - Rafida, Alifa Exa (Fakultas Keguruan dan Ilmu Pendidikan Universitas Kristen Satya Wacana, 2023)
Academic achievement is a crucial aspect in the field of education. This research aims to explore the improvement of academic achievement among fourth-grade students in the subjects of Natural Sciences and Social Sciences (IPAS) through the implementation of the Team Games Tournament (TGT) teaching model at SD Muhammadiyah Ambarbinangun Yogyakarta. The experimental approach is employed as the research method, with the research subjects consisting of 29 students in class IV A and 30 students in class IV B at SD Muhammadiyah Ambarbinangun Yogyakarta. Data analysis is conducted using descriptive statistical techniques. The research findings indicate that the application of the Team Games Tournament (TGT) teaching model has a positive impact on students' academic achievement in the IPAS subjects. There is a significant improvement in student participation, particularly through interaction and group work, creating a more engaging learning environment. These findings are supported by statistical analysis, revealing a significant difference in academic achievement before and after the implementation of the TGT model.